The Implementation of Residential Projects on Sulaimani Master Plan - Sangawi, Maryam Adnan; Ali, Alan Faraydoon (Kurdistan Journal of Applied Research, 2020)
Urban planning is a science that is reflected in the methods of land uses especially housing use, which is one of the most important sector in the city. It is considered the most important human requirement after food and wearer. The master plan is considered as one of the most important urban frame. It contains all the structural plans to control the urban expansion of all service sectors for the land uses in the city. It is planned for present and future status for the cites. The city master plan guarantees the equal distribution of urban land expansion from all sides. It secures the provision and implementation of housing projects to all residents in the city, Because of the economic growth that the city of Sulaimani witnessed after 2003. The city was suffering from a lack of attention to the issue of preparing a master plan. It did not have a master plan except for old studies that were carried out by the federal government. The master plan studies began from 2006 to 2009, then in 2009 it was recognized. Therefore, this subject is very substantial and the problem is that the implementation and site projection of housing was done in unappropriate manner with the stages of the master plan and the absence of evidence to invest in a housing sector. The purpose of this study is to identify a clear vision of housing investment projects, and shed the light on the necessary policies to be considered. Geography information system has been used to indicate the locations of housing projects in the city of Sulaimani. There is conformity with allocated lands for housing in the master plan. Then questions were addressed to specialists and agencies who had worked in housing projects such as the Directorate of Housing, Directorate of Investment, and the municipality. The questionnaire was proven after seeking the assistance of 9 experts to know the extent of the credibility of the questions that were laid down. The research found there are non-planning factors that affect the implementation of housing projects. Absence of laws and administrative errors in the implementation of housing projects playing the main role of having no clear housing implementation vision.